Influence of a mandibular fixed orthodontic retainer on periodontal health - Kaji Akihiko; Sekino Satoshi; Ito Hiroshi; Numabe Yukihiro (Sciendo, 2013)
Objective: To investigate the impact of bonded mandibular orthodontic retainers on local periodontal health.